2023
DOI: 10.3390/su15054606
|View full text |Cite
|
Sign up to set email alerts
|

Mediated Effect of Entrepreneurial Education on Students’ Intention to Engage in Social Entrepreneurial Projects

Abstract: Social enterprises are gaining great importance, since they can efficiently solve social problems and help reduce unemployment. Thus, it is important to discover how social entrepreneurial intention (SEI) can be enhanced. In this paper, a model of the impact of entrepreneurial education (EE) on SEI is formulated by relying on the human capital theory. It is hypothesized that EE acts on SEI directly as well as indirectly by increasing the perceived importance of social entrepreneurship (PISE). The model was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Therefore, the positive influence of entrepreneurship education on SEI is also confirmed. Research by Rakicevic et al (2023) has supported this statement. The authors assert that entrepreneurship education plays an essential role that must be considered within the framework of SEI factors.…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, the positive influence of entrepreneurship education on SEI is also confirmed. Research by Rakicevic et al (2023) has supported this statement. The authors assert that entrepreneurship education plays an essential role that must be considered within the framework of SEI factors.…”
Section: Discussionmentioning
confidence: 62%
“…The factors were analyzed through multiple regression analysis and the results showed that the influence of entrepreneurial self-efficacy and entrepreneurial education are factors that contribute to helping young graduates have an entrepreneurial intention, while business networks and perceived university support were not significant. Rakicevic et al (2023) conducted a study on the impact that entrepreneurial education offered by universities has on the intention to do social entrepreneurship, based on the theory of human capital. The study was done on students from the Republic of Serbia, and Bosnia and Herzegovina.…”
Section: Mrjiam 223mentioning
confidence: 99%
“…Social entrepreneurship education in universities is important because it helps students to develop the knowledge and skills needed to create and manage sustainable social enterprises (Rakicevic et al, 2023). It also helps them to understand the complexities of social problems and how to develop innovative solutions that have a positive impact on society.…”
Section: Literature Review Of the Study 21 Social Entrepreneurship Ed...mentioning
confidence: 99%